Clinical and biochemical analysis in infection-associated stroke - Grau, Armin J.; Buggle, Florian; Steichen-Wiehn, Christianne; Heindl, Silke; Banerjee, Tomas; Seitz, Rainer; Winter, Ralph; Forsting, Michael; Werle, Egon; Bode, Christoph; Nawroth, Peter Paul; Becher, Heiko; et al. (Stroke, 1995)
Background and Purpose Currently, recent infection (primarily bacterial infection) is discussed as a risk factor for cerebrovascular ischemia. The aim of this study was to investigate whether the association of ischemic stroke with recent infection is restricted to stroke subtypes and whether recent infection influences the severity of the postischemic deficit; we also aimed to define biochemical pathways linking infection and ischemic stroke. - Methods Analyzing the data of a prospective case-control study, we classified the etiology of cerebrovascular ischemia on the basis of clinical, neuroradiological, sonographical, cardiological, and biochemical data in 159 patients without and in 38 patients with infection within 1 week before ischemia. We assessed the severity of neurological deficits using the Scandinavian Stroke Scale. - Results In patients with recent infection compared with patients without infection, the neurological deficit on admission was more severe (median of scores, 41 versus 30.5; P<.005), cortical infarcts in the middle cerebral artery territory were more frequent (60% versus 26%; P<.001), the prevalence of extracranial artery stenoses was lower (9% versus 26%; P<.05), and definite or presumed cardioembolic stroke was more frequent (34% versus 19%; P<.05), as was stroke from cervical artery dissection (8% versus 1.3%; P=.05). Serum levels of C-reactive protein were higher in patients with (20.7±26.8 mg/L) than in those without infection (9.2±23.7 mg/L; P<.01). - Conclusions Recent infection may be associated with a more severe postischemic deficit and with an increased risk of stroke from cardioembolic origin and from cervical arterial dissection.